MP12: Abdominal ultrasound image acquisition and interpretation by novice practitioners after minimal training on a simulated patient model. (May 2020) - Waterman, B.; VanAarsen, K.; Lewell, M.; Tien, H.; Myslik, F.; Peddle, M.; Doran, S.
Abstract : Introduction: The FAST exam – Focused Assessment with Sonography in Trauma - is a rapid test using ultrasound to identify sonographic evidence of hemorrhage within the abdomen. In the prehospital setting, the information from a FAST examination can help triage patients, direct patients to the most appropriate facilities, assist with management strategies and potentially expedite time to definitive intervention. Few studies examine the accuracy of paramedic-only-performed FAST examinations. However, despite the potential benefits to the Canadian prehospital system, a potential barrier to implementation is the tremendous financial and operational burden if paramedics require prolonged ultrasound training courses. In this study, we conducted a double-blinded observational study comparing the accuracy of paramedic-performed FAST versus physician-performed tests on a sonographic Phantom, after a one-hour didactic training session. Methods: The interpretation of paramedic performed FAST exams was compared to the interpretation of physician performed FAST examinations on a mannequin model. The mannequin utilized in this study was a realistic model of a human torso where fluid could be injected into the abdomen to create a realistic ultrasound image of abdominal free fluid. Participants were required to scan the mannequin twice, once with 300 mL of fluid instilled and once with the abdomen free of fluid. Participants were blinded to the status of hemoperitoneum. The primary outcome of the study was accuracy rate of FAST examination by paramedics compared to emergency room physicians. Results were compared using the Chi-square test. Differences in accuracy rate were deemed significant if p < 0.05. Total scan time was reported using means, standard deviations and 95% CIs and was compared between groups using standard t-test. Results: Fourteen critical care flight paramedics and four emergency physicians were voluntarily recruited. The critical care paramedics were ultrasound-naive whereas the emergency physicians had ultrasound training. The correct interpretation of FAST scans was comparable between the two groups 85.6% and 87.5% (Δ1.79 95%CI -33.85 to 21.82, p = 0.90) for paramedics and emergency physicians respectively. Total scan time differed between groups but did not reach statistical significance. Paramedics took longer to complete the FAST examination with a mean (SD) time to complete the two scans of 10.35 (3.43) minutes compared to 7.34 (2.74) minutes for physicians, (Δ3.01 minutes 95%CI -0.97 to 7.00, p = 0.13). Conclusion: This study determined that critical care paramedics were able use ultrasound to detect free fluid on a simulated mannequin model and interpret the FAST exam with a similar accuracy as experienced emergency physicians following a one hour training course. This suggests the potential use of ultrasound in prehospital programs to determine the most appropriate transport destination and aid in the triage of trauma patients while limiting the financial and logistical burden of ultrasound training.